Measuring Social Capital and Proximimty - Stanislaw Walukiewicz (European Regional Science Association (ERSA), 2010)
A question how to position and measure the value of social capital (SC) of a company, country or region has come to predominate the debate over society and governance. We argue that social capital is of static or dynamic nature. We provide a tool to suitably measure it under both concepts. Also, we demonstrate that it is proximity that plays an inestimable role in the analysis of social capital, be it at a company or country level. We introduce the concept of orthogonality in social sciences (static approach), known as the Orthogonality Principle: Two forms A and B are orthogonal or disjoint if and only if there exists a simple, one-dimensional decision rule of yes-no type by which we can decide whether an object from an analysed universe X belongs to A or B. Such a decision rule exists in relation to tangibles and intangibles of a given firm or country and demonstrate that they are mutually orthogonal, which means that both categories of assets can be added regardless of the measure (money, points scores, etc.). This will not be the case of formal and informal relations, important components of social capital. We describe four forms of capital as financial, physical, human and social and prove that they are mutually orthogonal. We postulate that the value of a firm/country (the value of its entire capital) is an aggregate value of the four components above. We introduce the concept of new GDP and describe how to evaluate it and compare with the GDP model used today. We argue (dynamic approach) that the Virtual Production Line, defined by us in 2006, is a good tool to study proximity, a concept introduced by the French proximity school. Like capital, proximity is complex and multidimensional, and depends on time. We propose that there are four forms of proximity: cognitive, emotive, spatial and organizational. By the Orthogonality Principle, we prove that they are mutually orthogonal. We also suggest methods to evaluate them based on that Principle. By an example we show how to measure trust on the country level, the main component of emotive proximity.
Keywords: 330